1997
DOI: 10.1111/j.1469-7793.1997.603bd.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional nicotinic ACh receptors on interneurones in the rat hippocampus

Abstract: Neuronal nicotinic ACh receptors (nAChRs) were studied in the rat hippocampal slice preparation using whole‐cell patch‐clamp recording techniques. Responses to ACh (100 μm) were detected on inhibitory interneurones in the CA1 field of the hippocampus proper and in the dentate gyrus, but not on principal excitatory neurones in either region. The different neuronal types were identified based on their morphology and location. ACh excited interneurones in the hippocampus and dentate gyrus in current‐clamp recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
206
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(231 citation statements)
references
References 20 publications
22
206
3
Order By: Relevance
“…Depending on their electrophysiological and pharmacological properties they can be classified in at least three different receptor subtypes (Alkondon et al, 1993, Jones and Yakel, 1997, Buhler and Dunwiddie 2001. Based on results presented in this study, α2 containing nAChRs can be found in at least one subpopulation of GABAergic interneurons in cortical layer V and VI and hippocampal stratum oriens during postnatal development and in the adult.…”
Section: Expression Of Nachr α2 Mrna During Developmentmentioning
confidence: 66%
“…Depending on their electrophysiological and pharmacological properties they can be classified in at least three different receptor subtypes (Alkondon et al, 1993, Jones and Yakel, 1997, Buhler and Dunwiddie 2001. Based on results presented in this study, α2 containing nAChRs can be found in at least one subpopulation of GABAergic interneurons in cortical layer V and VI and hippocampal stratum oriens during postnatal development and in the adult.…”
Section: Expression Of Nachr α2 Mrna During Developmentmentioning
confidence: 66%
“…These findings suggest that activation of α7 receptors could influence GABA release in the hippocampus. Physiological studies in rat hippocampal slices have confirmed the presence of α7 receptors on interneurons in all layers of area CA1 (Alkondon et al, 1998;Buhler and Dunwiddie, 2001;Frazier et al, 1998b;Frazier et al, 1998a;Jones and Yakel, 1997;McQuiston and Madison, 1999) as well as GABA-mediated inhibition of CA1 pyramidal cells following activation of α7 receptors on CA1 interneurons (Alkondon and Albuquerque, 2001;Buhler and Dunwiddie, 2002;Ji and Dani, 2000). It seems reasonable to hypothesize that α7 receptors may also modulate GABA release from interneurons in hippocampal area CA3 given that α-BTX binding has been observed on CA3 interneuron subtypes (Freedman et al, 1993) that are known to make synaptic contact with CA3 pyramidal cells (Freund and Buzsaki, 1996).…”
Section: Altered Gaba Releasementioning
confidence: 93%
“…In addition, nAChRs can modulate GABAergic transmission in multiple brain areas, such as thalamus, cortex, hippocampus, and interpeduncular nucleus (Lena et al, 1993;Alkondon et al, 1997Alkondon et al, , 2000Lena and Changeux, 1997;Fisher et al, 1998;Radcliffe et al, 1999). Modulation of GABA neurons by nAChRs has been most extensively studied in the hippocampus, where GABAergic interneurons express multiple nAChR subtypes (Alkondon et al, 1997;Jones and Yakel, 1997;Frazier et al, 1998b;McQuiston and Madison, 1999;Ji and Dani, 2000). The physiologic impact of nAChR activation is critically dependent upon their localization.…”
Section: Nicotinic Modulation Of Gabaergic Transmission In the Vtamentioning
confidence: 99%